2016
DOI: 10.1097/igc.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Appendiceal Lesions in Appendicectomies Performed During Surgery for Mucinous Ovarian Tumors: A Retrospective Study

Abstract: Given the prevalence of coexisting appendiceal pathology found in this study and the reported low rates of complications associated with the procedure, an appendicectomy is recommended in the management of all mucinous ovarian neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Feigenberg et al reported similar results, in that final pathology in all cases with normal looking appendix were negative (10). Moore et a1 also confirmed this result (2).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Feigenberg et al reported similar results, in that final pathology in all cases with normal looking appendix were negative (10). Moore et a1 also confirmed this result (2).…”
Section: Discussionsupporting
confidence: 77%
“…It is being thought that severe military conflicts in Africa shorten the expected lifetime for more than 2 years. In general, WHO had calculated that 269 thousand people had died in 1999 due to the effect of wars and that loss of 8.44 million healthy years of life had occurred (2,3). Wars negatively affect the provision of health services.…”
Section: War and Women's Healthmentioning
confidence: 99%
“…The intraoperative findings in the appendix may be subtle, and many surgeons opt to perform appendectomy if the frozen section shows a mucinous neoplasm, whether benign, borderline, or overtly malignant, in the ovary, even if the appendix appears grossly unremarkable. [15][16][17] Pancreatobiliary carcinomas metastatic to the ovary are relatively uncommon, presenting at a mean age of 58 to 59 years, and pose a unique diagnostic challenge on frozen section by having deceptively bland cytologic features, referred to as maturation phenomenon. [18][19][20] Most cases (.80%) are bilateral, with a mean size of 10 cm.…”
Section: Mucinous Tumors-primary Ovarian Versusmentioning
confidence: 99%